Hubungan Pengetahuan Ibu Hamil Tentang Triple Eliminasi dengan Kepatuhan Pemeriksaan di Puskesmas Tampo Kabupaten Banyuwangi Tahun 2023 - Shinde Yunita; Rima Nur Khasanah; Desy Purnamasari (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2024)
Pregnant women are one of the populations at risk of contracting Human Immunodeficiency Virus (HIV), Syphilis, and Hepatitis B. The risk of mother-to-child transmission for HIV/AIDS is 20%-45%, for Syphilis is 69-80%, and for Hepatitis B it is more than 90%. Transmission of HIV, Syphilis and Hepatitis B from mother to child results in morbidity, disability and death. The aim of this research is to determine the relationship between pregnant women's knowledge about Triple Elimination and compliance with examinations at the Tampo Health Center, Banyuwangi Regency in 2023. The research design is a correlation analytical cross sectional study approach, the population is pregnant women in the 2023 Tampo Health Center working area, totaling 390 pregnant women using an accidental sampling technique. . The number of samples taken was 66 pregnant women. Statistical tests use Chi-Square and Mann-Whitney U with a significance level of 0.05 with SPSS. The research results showed that most of the pregnant women's knowledge about Triple Elimination was in the sufficient category, namely 36 respondents (54.5%), and compliance with the Triple Elimination examination at the Tampo Community Health Center was mostly in the Obedient category, namely 48 respondents (72.7%). There is a relationship between pregnant women's knowledge about Triple Elimination and compliance with examinations at the Tampo Health Center in 2023 (p-Value 0.023 < 0.05). The results of the research can provide additional knowledge so that in the future, if you become pregnant again, you can comply with the Triple Elimination examination and inform pregnant women to carry out the Triple Elimination examination.